Caries experience among adolescents in southeast Italy - Christian Napoli; Paolo Trerotoli; Giuliana Solinas; Guglielmo Campus; Laura Strohmenger; Paolo Castiglia; Maria Teresa Montagna (Elsevier, 2012)
Background/purpose: According to WHO recommendations, 12-year-olds are considered an important target group for evaluating the level of dental caries among children with permanent teeth, and are often chosen for international comparisons. The aim of the present study was to evaluate the current oral health status of 12-year-old children in southeast Italy, stratified by gender and residential area. Materials and methods: The survey was conducted on 431 children enrolled by multistage cluster sampling. A dental caries experience index (decayed, missing, and filled permanent teeth; DMFT) was recorded at schools by a team of examiners trained at the start of the study. Statistical analyses by Chi-square, Fisher's exact, and Wilcoxon tests were performed using SAS version 9.1 software for PCs. We applied the Zero-Inflated Negative Binomial regression model in the STATA package. Results: Caries prevalence was recorded in 38.3% of the sample. Estimated means and 95% confidence intervals of the DMFT index by gender were: 1.15 (0.91-1.39) for males, 1.26 (1.02-1.5) for females, and 1.21 (1.03-1.39) for the total sample. The D component of the index was dominant. The mean number of caries found in southeast Italy was significantly higher than the national mean (t=3.125, P=0.002), but significantly lower than the mean for south Italy (t=−2.125, P=0.03). Results of the regression model showed that only the mother and father's nationality and educational level contributed to the DMFT. Conclusions: The oral health situation of 12-year-old children from southeast Italy seems to be in line with that in other Western European countries.